Paradoxical effects of principals’ leadership strategies on islamic character development in multicultural school settings - Fatmaya Anisa Rahmania; Ifada Novikasari (Islamic perspective on Communication and Psychology, 2025)
Background: The leadership of school principals plays a crucial role in shaping students' character in multicultural environments such as SMK Negeri 1 Purwokerto. However, there has been no specific study that examines the influence of leadership strategies on the development of students’ Islamic character within the context of cultural and religious diversity. This study addresses that academic gap by integrating three aspects: leadership strategies, Islamic character, and the multicultural context. Methods: This is an associative quantitative study employing a field research approach. A sample of 80 students was selected from a population of 403 students in grades X and XI using simple random sampling. Data were collected through interviews, observations, and Likert scale-based questionnaires, and were then analyzed using validity, reliability, normality, linearity, and simple linear regression tests. Findings: The findings indicate that the instrument was valid (r-count > 0.2199) and reliable (Cronbach’s Alpha: X = 0.742; Y = 0.729). The data were normally distributed (sig. = 0.168) and exhibited a significant linear relationship (sig. = 0.001). Simple linear regression analysis revealed that leadership strategies had a substantial influence on Islamic character (sig. = 0.003), but the effect was negative (regression coefficient b = -0.244) with a low contribution (R² = 0.105). This suggests that an increase in leadership strategies may potentially decrease Islamic character, possibly due to a lack of collaborative approaches or the dominance of external factors (89.5%). Conclusion: The conclusion highlights the significance of transformative-relational leadership, which entails embodying Islamic values and conducting contextual evaluations in multicultural settings. Novelty/Originality of this article: The novelty of this study lies in the integration of the three aspects and the revelation of a paradoxical negative relationship that has not been explored in previous research.